Evaluation of Skew-planar Antenna for UAV Communication at 2.4 GHz Band - T Prakoso; A A Yaqin; Ibrahim Ibrahim; I Santoso; A Triwiyatno; M A Riyadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Skew-planar antenna is suitable for unmanned aerial vehicles (UAVs) since it has circular polarization (avoiding polarization-mismatched), omnidirectional radiation pattern (low pointing loss) thus comply with maneuver angles of UAV, and also small size. Investigation with electromagnetic simulations shows that tilt angle and coaxial length are the most sensitive parameters. Modified design with 55° tilt angle (original design: 45°) and 100 mm coaxial length (original: 60 mm) potentially provides wider bandwidth (400 MHz vs. 290 MHz), better impedance-matched (|S11|: -47.1 dB vs. -13.6 dB), and better gain (1.98 dBi vs 1.61 dBi). The antenna is predicted capable to support service distance of 3 km in 2.4 GHz band if used with communication module with 18 dBm transmit power and -100 dBm receiver sensitivity. Therefore, the modified antenna is suitable to be applied in UAV.